2015
DOI: 10.15285/ebd.55126
|View full text |Cite
|
Sign up to set email alerts
|

Sınıf Öğretmenlerinin Denetim Sürecine İlişkin Algı ve Beklentilerinin Metaforlar Aracılığı ile Belirlenmesi

Abstract: ÖzetDenetim sürecinin öğretmenin yargılanması olduğu düşüncesi, artık yerini çağdaş denetim yaklaşımının özünü oluşturan öğretmene meslekte yol göstericilik ve yardım düşüncesine bırakmıştır. Denetim sürecinin sağlıklı bir şekilde işlemesi, öğretmenlerin bu sürece ilişkin algılarının ne olduğunun bilinmesiyle mümkün olmaktadır. Bu araştırmada öğretmenlerin denetim sürecine ilişkin algıları ile denetim sürecinden beklentileri metaforlar aracılığı ile belirlenmeye çalışılmıştır. Bu amaç doğrultusunda öğretmenler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Results of this metaphor-based study show that primary school teachers have mostly negative perceptions of supervisors. Most studies conducted in Turkey have reported similar conclusions (Boydak, Özan & Şener, 2015;Kocabaş & Özdemir, 2010;Sünbül & İnandı, 2005;Töremen & Döş, 2009). As supervision is an activity for developing education, the relationship between teachers and supervisors must be established soundly.…”
Section: Discussion and Recommendationsmentioning
confidence: 67%
“…Results of this metaphor-based study show that primary school teachers have mostly negative perceptions of supervisors. Most studies conducted in Turkey have reported similar conclusions (Boydak, Özan & Şener, 2015;Kocabaş & Özdemir, 2010;Sünbül & İnandı, 2005;Töremen & Döş, 2009). As supervision is an activity for developing education, the relationship between teachers and supervisors must be established soundly.…”
Section: Discussion and Recommendationsmentioning
confidence: 67%